Challenges for corporate social responsibility practices - Rodrigues , António Augusto Baptista (2023)
Corporate social responsibility (CSR) is an expression used by companies to show that they are aware that their role in society or in the community in which they operate is not just to seek profit.According to the European Commission (2011), corporate social responsibility is defined as "the responsibility of companies for the impact they have on society.The pandemic has challenged many companies and economies and affected millions of people, emphasizing the need for collaboration and alignment between economic activity and human needs. It is time for all companies to put into practice actions that honor the purpose and organizational values that are intrinsic to their “personality” and that reflect the willingness to work with others to solve the great problems of our world, simultaneously building and building trust. much needed in our society.To analyze the challenges facing social responsibility practices, a qualitative methodology was used, through the literature review method, using various sources: scientific articles, legislation and other technical-scientific documentation.This descriptive article contributed to the debate in which CSR is a matter of attitude, apart from the fact that each company does what it can according to its resources; because it is not a matter of social action, but of social responsibility. The social responsibility is a more global and larger concept than social action.The main conclusion suggests that the actions that business leaders take today will be decisive so that, in the near future, they can look back and feel proud and satisfied with what they have done. What is done today, in terms of social responsibility, will define the value and reputation of the company, strengthening its purpose and values. It is therefore an investment worth betting on.The Sustainable Development Goals (SDG) are also an opportunity for companies to expand Corporate Social Responsibility (CSR), an initiative that constitutes one of the global efforts to translate sustainable development into something concrete and measurable.